The effects of doubling instruction efforts on middle school students' achievement: Evidence from a multiyear regression-discontinuity design - Timothy J. Bartik; Marta Lachowska (W.E. Upjohn Institute for Employment Research, 2014)
We use a regression-discontinuity design to study the effects of double blocking sixth-grade students in reading and mathematics on their achievement across three years of middle school. To identify the effect of the intervention, we use sharp cutoffs in the test scores used to assign students to double blocking. We find large, positive, and persistent effects of double blocking in reading, but, unlike previous research, we find no statistically significant effects of double blocking in mathematics either in the short run or medium run.
Keywords: I21; C21; 330; Regression discontinuity; Double blocking; Middle school